Legal Study of the Defects in Amendments to the Articles of Association of Limited Liability Companies in Voting at General Meetings of Shareholders - Abdullah, Ali; Nadhifa Putri Kinasih (Inovasi Pratama Internasional. Ltd, 2025)
Law Number 40 of 2007 concerning Limited Liability Companies and the Company's Articles of Association The General Meeting of Shareholders (GMS) is the highest organ in a limited liability company that has the authority to decide on various strategic matters, including changes to the articles of association and replacement of members of the Board of Directors and its decisions are based on the quorum of attendance of shareholders. If there is a change to the articles of association, then referring to the GMS, it must meet the requirements of Article 88 of Law Number 40 of 2007 concerning Limited Liability Companies which states that decisions can be taken if the meeting is attended by at least 2/3 (two-thirds) of shareholders with voting rights. The normative legal research method is used to examine the applicable laws and regulations and their application in practice. The results of the study indicate that the judge's decision ignores the provisions of the attendance quorum, but this study found that the judge in deciding and determining the presence of shareholders must be taken unanimously. This has the potential not to provide legal protection and certainty so that it will harm the shareholders in the company.